Myanmar State,Society and Ethnicity - N. Ganesan (Iseas, 2007)
Focusing on some of the most important and topical questions about Myanmar, contributors to this book look at issues of historical influence and political considerations that have shaped the dominant thinking within the state and the military. There are equally important studies of sensitive topics like the political economy of the state and the level of human security in the country. The three ethnics groups--Karen, Kachin, and Shan--are also studied in detail. Some of the negotiations between the Karen and Kachin ethnic insurgent group representatives on the one hand, and the military junta on the other, are spelled out in detail. An important corollary finding is the importance of religion and religious personalities in brokering peace between the ethnic groups and the military government. Finally, the book deals with how the various ethnic groups are trying to cope with decades of conflict and reconstruct their communities.